Tree seeds for free - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
Over the past three years, the Henry Doubleday Research Association (HDRA) has been running a successful initiative to select and supply seeds of tree and shrub species to groups involved in tree planting in developing countries. Under this...